The Leadership Philosophy of Tau Samawa - Hendra Jaya; Muh Hambali; Nensy Setyaningrum; Nur Wasliah (International Journal of Religious and Cultural Studies, 2023)
This research aims to explore and construct leadership values ​​based on Tau Samawa culture. This research employed a literature review method. It is found that the current leadership in in crisis. The results shows that Tau Samawa as local wisdom has seven leadership philosophies as stated in the Musakara Rea Minutes of the Samawa Traditional Institute. These are Pamendi to Panyadu, mutual pedi', Saling Satingi, Saling Tulung, Saling Satotang, Saling Sayaman Ate, Adab Edab Boa Ela, and Satemung. These leadership philosophies are very much needed in building a human civilization that has a national religious character, since they manifest in leadership characters, namely religious, caring, sensitive, and most importantly, these philosophies will create leaders who are able to balance heart, mind, words, and actions.